Daivavyapashraya Chikitsa- A Preventive Strategy to Deal Maternal Stress - Viva Myalil Vasu,; Leena Parameswaran Nair,; Haritha Chandran,; Meera Esanamangalam, (International Journal of Ayurveda and Pharma Research, 2024)
Maternal stress is a potential risk factor for the onset of neurodevelopmental disorders. These days, prenatal check-ups just look at women's physical health concerns. It is crucial to remember that a variety of stress, anxiety, and depressive symptoms, such as a strained relationship with one's spouse, can also have an impact on fetal development, in addition to diagnosable illnesses. It is very well highlighted in Ayurveda with the concept of Satva Vaisheshyakara Bhaavas, which says that, the psychological makeup of the offspring is influenced by various factors, such as the mother's mental health and what she hears, while she is pregnant. Through Mantra, Mani, Mangala, Bali, Homa, Upavasa and other healing techniques, Daivavyapashraya Chikitsa is an Ayurvedic therapy method, that promotes spiritual health and helps manage mental stress by dispelling negativity and fear and replacing it with a sense of optimism and control. Additionally, this Chikitsa has several logical traits that are consistent with the Theory of Cognitive Adaptation, which holds that, people create positive delusions as a defensive mechanism to shield their mental health from outside threats. With a scientific justification, this article seeks to highlight the potential advantages of Daivavyapashraya Chikitsa in lowering maternal stress.